2016
DOI: 10.1116/1.4942202
|View full text |Cite
|
Sign up to set email alerts
|

Computer modeling of angular emission from Ag(100) and Mo(100) surfaces due to Arn cluster bombardment

Abstract: Defects and morphological changes in nanothin Cu films on polycrystalline Mo analyzed by thermal helium desorption spectrometry Molecular dynamics computer simulations are employed to investigate the effect of projectile size and surface morphology on the angular emission stimulated by impact of Ar gas cluster projectiles. Argon clusters of sizes n ¼ 10-1000 and kinetic energies of 10 and 20 keV Ar n aimed at normal incidence are used to sputter Ag(100) and Mo(100) samples. The total sputtering yield is larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The simulation results showed that many atoms are sputtered as dimers, trimers and larger clusters that can rotate around the center of mass, which is in a good agreement with the results by other authors [5]. The number of such sputtered clusters for the Cu target is much higher than that for the Mo one.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The simulation results showed that many atoms are sputtered as dimers, trimers and larger clusters that can rotate around the center of mass, which is in a good agreement with the results by other authors [5]. The number of such sputtered clusters for the Cu target is much higher than that for the Mo one.…”
Section: Resultssupporting
confidence: 89%
“…Note that the similar distributions were observed for bombardment of Ag(100) surface by Ar clusters [5]. The centers of spots visible in Fig.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations